Integration of Local Cultural Knowledge in the Community Products Design and Development - Hoaihongthong, Suwannee; Tuamsuk, Kulthida (Journal of Ecohumanism, 2024)
integration of local cultural knowledge in community products through the framework of cultural capital and wisdom across eight categories. A qualitative method involved in-depth interviews with 30 individuals, including 15 entrepreneurs and 15 cultural experts selected from five target communities. The findings reveal the context of local cultural knowledge available in the communities, and the integration of local cultural knowledge being integrated into the community product development processes. It is also found that despite the presence of diverse local cultures, these cultural resources are underutilized in product design and development due to a lack of knowledge and awareness regarding the significance of product identity.